Elucidating different roles of solvent additives in organic photovoltaics under solar and indoor light emission environments - Jeon, Gyeong G.; Kim, Jinseck; Eun, Hyeong Ju; Ha, Jong Woon; Chung, Sein; Shin, So Jeong; Cho, Kilwon; Yoon, Sung Cheol; Kim, Bumjoon J.; Ko, Seo Jin; Kim, Jong H. (Chemical Engineering Journal, 2024)
Incorporation of solvent additive in bulk heterojunction layer has been effective method for the optimization of film morphology and crystallinity, enabling high efficiency organic solar cells under standard 1 SUN illumination. However, the effects of the additives in low-intensity indoor light environment have not been investigated much so far. In this study, a new donor polymer (PBz-ET) having an efficient spectral matching with LED was synthesized and employed. Moreover, we elucidate the different roles of additives for organic solar cell operations depending on 1 SUN and low-intensity LED illuminations. Through systemic characterizations on morphology, crystallinity, and electrical properties, we found that the additive boosting nanoscale phase separation is compatible for the organic solar cells working in 1 SUN illumination while the additive being capable of increasing crystallinity is more adaptable to those used for indoor light environment. The results in this study suggest a rational selection rule of additives for designing organic solar cells in different light environments.
Keywords: Cristallinity; Indoor light environments; Light intensity; Low light; Low-intensity; Low-light intensity; Organic photovoltaics; Role of solvents; Solar light; Solvent additives; Additives; Crystallinity; Low-light intensity; Organic solar cells; Phase separation